Ideological Control against Heteronormativity in Forster's 'Maurice' - Raissa Rahmania Putri; Dian Nurrachman; Ice Sariyati (Lakon : Jurnal Kajian Sastra dan Budaya, 2024)
Set in Victorian to Edwardian England, the novel features a character with a homosexual identity, prompting this research on the character's non-conformity to heteronormative standards. This article aims to analyze the form of ideological control that emerges as the heteronormative norm in the novel Maurice through the perspective of class-consciousness Marxist, using Eagleton’s Ideology theory. Ideological theory through Marxist concepts, reveals context-based analysis of how economic structures shape ideology and social change. This article uses a descriptive-qualitative method with a mimetic approach, which describes the data collected through narration and dialogue from the novel. The findings categorize heteronormative norms as ideological control into three types: those stemming from religious dogma, the hegemony of masculinity in public schools, and the discourse on sexuality. Maurice explained the causal relationship between class position in the social strata and dominant norms, impacting the characters' lives.